AMP-Activated Protein Kinase Activation Leads to Lysome-Mediated NA+/Iˉ-Symporter Protein Degradation in Rat Thyroid Cells - Cazarin, J. M.; Andrade, B. M.; Carvalho, D. P. (Hormone and Metabolic Research, 2014)
Iodide uptake by thyroid cells is mediated by a transmembrane glycoprotein known as the Na+/I−-symporter (NIS). NIS-mediated iodide uptake plays important physiological role in thyroid gland function, as well as in diagnostic and treatment of Graves’ disease and thyroid cancer. Although different studies investigated the transcriptional mechanisms of NIS expression, there is no report on the NIS post-translational regulation related to NIS protein degradation in thyroid cells. Recently, our group showed that AMP-activated protein kinase (AMPK) plays a pivotal role in the rat thyroid gland, downregulating iodide uptake, NIS protein, and mRNA content. Since several studies demonstrated that AMPK regulates post-transcriptional mechanisms, such as autophagy-mediated processes in different tissues, we hypothesized that AMPK activation could also regulate NIS protein degradation through the lysosome pathway in thyroid cells. Rat follicular thyroid PCCL3 cells cultivated in Ham’s F12 supplemented with 5% calf serum and hormones were exposed to the AMPK pharmacological activator 5-aminoimidazole-4 carboxamide ribonucleoside (AICAR), in the presence or absence of Bafilomycin A1 or MG132 for 24 h. Treatment of PCCL3 cells with Bafilomycin A1 fully prevented the decrease of iodide uptake and NIS protein content mediated by AMPK activation. In contrast, the treatment with MG132 was unable to prevent the effects of AMPK activation on NIS. Our results show that AMPK activation significantly induces NIS protein degradation through a lysosome-mediated mechanism.
Keywords: AMPK; Bafilomycin A1; iodide uptake; NIS degradation